In Liquido Computation with Electrochemical Transistors and Mixed Conductors for Intelligent Bioelectronics. Issue 15 (22nd February 2023) - Cucchi, Matteo; Parker, Daniela; Stavrinidou, Eleni; Gkoupidenis, Paschalis; Kleemann, Hans
Abstract: Next‐generation implantable computational devices require long‐term‐stable electronic components capable of operating in, and interacting with, electrolytic surroundings without being damaged. Organic electrochemical transistors (OECTs) emerged as fitting candidates. However, while single devices feature impressive figures of merit, integrated circuits (ICs) immersed in common electrolytes are hard to realize using electrochemical transistors, and there is no clear path forward for optimal top‐down circuit design and high‐density integration. The simple observation that two OECTs immersed in the same electrolytic medium will inevitably interact hampers their implementation in complex circuitry. The electrolyte's ionic conductivity connects all the devices in the liquid, producing unwanted and often unforeseeable dynamics. Minimizing or harnessing this crosstalk has been the focus of very recent studies. Herein, the main challenges, trends, and opportunities for realizing OECT‐based circuitry in a liquid environment that could circumnavigate the hard limits of engineering and human physiology, are discussed. The most successful approaches in autonomous bioelectronics and information processing are analyzed. Elaborating on the strategies to circumvent and harness device crosstalk proves that platforms capable of complex computation and even machine learning (ML) can be realized in liquido using mixed ionic–electronic conductors (OMIECs). Abstract : Organic electrochemical transistors (OECTs) have emerged as ideal elements for a multitude of applications in bioelectronics. However, integration of multiple OECTs is still challenging because the electrolyte "shorts" all the devices producing unwanted crosstalk. Such crosstalks are explained and modeled and strategies to avoid it, or alternatively, to harness it in order to produce intelligent bioelectronics are discussed.